Effectiveness of Community-Based Interventions for Improving Maternal and Child Health Outcomes in Low-Middle-Income Areas in Pakistan - Javaid, Usman; Javed, Humera; Mushtaq, Umair; Arooj, Taha; Shamraz, Hinza (Biological and Clinical Sciences Research Journal, 2025)
Maternal and child health (MCH) outcomes remain a major public health concern in Pakistan, particularly in low- and middle-income areas where access to health services is limited. Objective: To assess the effectiveness of community-based interventions in improving maternal and child health outcomes in underserved areas of Pakistan. Methods: This cross-sectional analytical study was conducted at Services Hospital, Lahore, from November 2024 to April 2025. A total of 245 participants, including pregnant women, mothers of children under five years, and primary caregivers. Data were collected using a structured questionnaire on maternal health practices, child health indicators, and exposure to community-based interventions such as lady health worker visits, counseling sessions, and health education campaigns. Results: Among participants, 77.1% reported at least one ANC visit, while 51.4% completed four or more visits. Institutional deliveries were recorded in 61.6%, and PNC within 48 hours in 43.7%. Immunization coverage was 74.7%, and exclusive breastfeeding was practiced in 59.2% of cases. Exposure to CBIs was significantly associated with better outcomes: ≥4 ANC visits (64.8% vs. 34.1%, p < 0.01), institutional delivery (71.2% vs. 46.8%, p < 0.01), full immunization (82.1% vs. 61.9%, p < 0.01), and exclusive breastfeeding (65.7% vs. 47.2%, p = 0.02). Logistic regression confirmed independent associations between CBI exposure and improved maternal and child health outcomes. Overall satisfaction with CBIs was high (72.6%), although some participants reported irregular visits and referral gaps. Conclusion: Community-based interventions significantly improve maternal and child health outcomes in low- and middle-income areas of Pakistan.